PROFIL PRAMUSAJI HOTEL BINTANG EMPAT KOTA PADANG - Yusra, Widya; Kasmita, Kasmita; Waryono, Waryono (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
The purpose of research isto know the waiter/ waitress profile four star Hotel Padang to see from 5 indicators. This study is a descriptive correlational cuantitative study. The population in this research iswaiter and waitressfood & beverage service four star Hotel Padang for 39 persons. Sample selection techniques in the study using total population.Data collection techniques with a structured questionnaire based on Likert scale that has been tested for validity and reliability. Research results show is: 1) Education background of waiter/waitress is SMA/SMK level as big as 58,97 %, 2) Work experience in the range 1-5 years as big as 69,23%,3) Work competen is haven’t profession sertification as big as74,36%,4) Performance waiter is sufficient with an average value 31,54 in the range 31,25-35,75 and performance waitress is sufficient with an average value 35,73 in the range 31,85–36,15,5) Attitude is sufficient with an average value60,79 in the range 55,5 – 62,5. Keywords:profile, waiter/waitress,hotel